Advances in fisheries economics : (Blackwell Pub, 2007)
The book brings together many of the world’s leading fisheries economists to authoritatively cover the many issues facing the field of fisheries economics and management today. The content is divided into four sections including property management; capital theory and natural resources; game theory and international fisheries; applied fisheries economics and management.